Variability in the Composition of Pacific Oyster Microbiomes Across Oyster Families Exhibiting Different Levels of Susceptibility to OsHV-1 μvar Disease - King, William L.; Siboni, Nachshon; Williams, Nathan L. R.; Kahlke, Tim; Nguyen, Khue Viet; Jenkins, Cheryl; Dove, Michael; O’Connor, Wayne; Seymour, Justin R.; Labbate, Maurizio (Frontiers in Microbiology, 2019)
Oyster diseases are a major impediment to the profitability and growth of the oyster aquaculture industry. In recent years, geographically widespread outbreaks of disease caused by ostreid herpesvirus-1 microvariant (OsHV-1 μvar) have led to mass mortalities among Crassostrea gigas, the Pacific Oyster. Attempts to minimise the impact of this disease have been largely focussed on breeding programs, and although these have shown some success in producing oyster families with reduced mortality, the mechanism(s) behind this protection is poorly understood. One possible factor is modification of the C. gigas microbiome. To explore how breeding for resistance to OsHV-1 μvar affects the oyster microbiome, we used 16S rRNA amplicon sequencing to characterise the bacterial communities associated with 35 C. gigas families, incorporating oysters with different levels of susceptibility to OsHV-1 μvar disease. The microbiomes of disease-susceptible families were significantly different to the microbiomes of disease-resistant families. OTUs assigned to the Photobacterium, Vibrio, Aliivibrio, Streptococcus and Roseovarius genera were associated with low disease resistance. In partial support of this finding, qPCR identified a statistically significant increase of Vibrio-specific 16S gene copies in the low disease resistance families, possibly indicative of a reduced host immune response to these pathogens. In addition to these results, examination of the core microbiome revealed that each family possessed a small core community, with OTUs assigned to the Winogradskyella genus and the Bradyrhizobiaceae family consistent members across most disease-resistant families. This study examines patterns in the microbiome of oyster families exhibiting differing levels of OsHV-1 μvar disease resistance and reveals some key bacterial taxa that may provide a protective or detrimental role in OsHV-1 μvar disease outbreaks.